Assimilate highway to sink organs - Physiological consequences of SP6A overexpression in transgenic potato (Solanum tuberosum L.) - Lehretz, Günter; Sonnewald, Sophia; Sonnewald, Uwe (Journal of Plant Physiology, 2021)
Leaf/stem-specific overexpression of SP6A, the FLOWERING LOCUS T homolog in potato (Solanum tuberosum), was previously shown to induce tuberization leading to higher tuber numbers and yield under ambient and abiotic stress conditions. In this study, we investigated the mechanism underlying SP6A action. Overexpression of SP6A reduced shoot growth, mainly by inhibition of stem elongation and secondary growth, and by repression of apical bud outgrowth. In contrast, root growth and lateral shoot emergence from basal nodes was promoted. Tracer experiments using the fluorescent sucrose analogue esculin revealed that stems of SP6A overexpressing plants transport assimilates more efficiently to belowground sinks, e.g. roots and tubers, compared to wild-type plants. This was accompanied by a lower level of sucrose leakage from the transport phloem into neighboring parenchyma cells and the inhibition of flower formation. We demonstrate the ability of SP6A to control assimilate allocation to belowground sinks and postulate that selection of beneficial SP6A alleles will enable potato breeding to alter plant architecture and to increase tuber yield under conditions of expected climate change.
CRIS-Team WoS Importer:2021-10-29